(untitled) (Research, Society and Development, 2023)
Orofacial harmonization (HOF) is a dental specialty that seeks to improve facial aesthetics through personalized procedures, such as facial filling, botulinum toxin and application of fibrin rich in leukocyte platelets (L-PRF). The treatments aim to achieve a balanced and rejuvenated appearance, enhancing the natural features of the face. Leukoplatelet aggregates, obtained from the patient’s own blood, have stood out in HOF, as they contain growth factors and cytokines that promote tissue regeneration. They are applied to stimulate collagen production, improve the texture and appearance of the skin, in addition to being used in biostimulation techniques for tissue regeneration and quality improvement. L-PRF, obtained through blood centrifugation, is an effective therapeutic option in HOF, as it contains growth factors, cytokines and bioactive proteins that promote cell regeneration, collagen production and improvement of local vascularization, resulting in an appearance rejuvenated and natural. The use of L-PRF in HOF represents an advanced and safe approach, taking advantage of the biological resources of the patient’s own body to enhance the aesthetic results. Thus, the objective of this research is to analyze and synthesize the available scientific evidence on the use of L-PRF in HOF.